2019
DOI: 10.4103/ijpvm.ijpvm_174_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D supplement on mood status and inflammation in Vitamin D deficient Type 2 diabetic women with anxiety: A randomized clinical trial

Abstract: Background: Vitamin D plays an important role in nervous health and depression. Vitamin D deficiency and anxiety affect diabetic status. The purpose of this study was to determine the effect of vitamin D supplementation on anxiety, depression, and inflammation in diabetic women with anxiety. Methods: In this randomized controlled trial, totally 51 women with type 2 diabetes (T2DM) and vitamin D deficiency were randomly allocated to receive one oral pearl of 50,000 IU vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…It also assessed the intensity of stress in the respondents' lives. However, this was not related to any degree with vitamin D levels [32].…”
Section: Stressmentioning
confidence: 69%
“…It also assessed the intensity of stress in the respondents' lives. However, this was not related to any degree with vitamin D levels [32].…”
Section: Stressmentioning
confidence: 69%
“…The basic details of the studies included in the systematic review [26][27][28][29][30][31] are presented in Table 2. The included studies that evaluated the influence of vitamin D supplementation on the mental health of diabetic patients were conducted mainly in Iran [29][30][31], and also in the United States of America [28], Canada [27], and the Netherlands [26]. The study sample comprised patients recruited from the specific clinics of the hospitals [27,29,31] or from general practitioners [26].…”
Section: Resultsmentioning
confidence: 99%
“…The included studies that evaluated the influence of vitamin D supplementation on the mental health of diabetic patients were conducted mainly in Iran [29][30][31], and also in the United States of America [28], Canada [27], and the Netherlands [26]. The study sample comprised patients recruited from the specific clinics of the hospitals [27,29,31] or from general practitioners [26]. Some groups were recruited to be characterized by specific diabetes complications, such as chronic kidney disease [27] or painful diabetic neuropathy [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our results showed that people with depression, anxiety, and insomnia take significantly more vitamin D ( Table 3 and Figure 1 ). Previous interventions have shown the impact of vitamin D deficiency on depression [ 50 , 51 ], however, limited studies have been carried out to illustrate the association of anxiety disorders with serum levels of vitamin D [ 52 ]. Penckofer et al reported that six-month intervention with 50,000 IU vitamin D significantly decreased depression and anxiety in people with type 2 diabetes mellitus (T2DM) who had depression [ 53 ].…”
Section: Discussionmentioning
confidence: 99%